The impact of loading activity toards water quality and ecosystem of Tasik Chini, Pahang - Siti Sarah , Kassim (2013)
This study was carried out in March, April and May 2013 during dry day and raining day to determine the impact of logging activities toward water quality and ecosystem of Tasik Chini, Pahang. The result for each parameter in water quality is classified based on National Water Quality Standard (NWQS) and Water Quality Index (WQI). A total of six sampling stations were selected for this study which are Laut Gumum, Laut Jerangking, Laut Kenawar, Laut Melai, Laut Pulau Balai and Resort Tasik Chini. Thirteen water quality parameters were analyzed based on in-situ and ex-situ analysis during two season's period. The methods used for laboratory analysis are based on APHA, HACH and IDEXX Colilert Methods. For physical parameter, the water quality findings were: turbidity (3.1-61.35 NTU), temperature (26.44-31.95 °C) and TSS (324.33mgIL). The findings for chemical parameter were BOD (1.6-7.55 mg/L), COD (13-67 mg/L), DO (2.75-8.38 mg/L), nitrate (0.01-0.14 mg/L), phosphate (0.01-1.23 mg/L), pH (4.96-6.48), ammoniacal nitrogen (0.007-0.073 mg/L), and electrical conductivity (16-35 RS/cm). The findings for biological parameter were total coliform (67-739 MPN/1 OOml) and E-coli (1.7-135.9 MPN/lOOml). The range of every parameter is higher during wet day compare to dry day. The water quality was majorly impacted at station Laut Jerangking due to nearest logging activities and rubber plantation while at station Laut Gumum due to nearest agricultural activities, palm oil plantation and settlement of indigenous people. From the analysis, the logging activities near Laut Jerangking did affected the water quality by physical, chemical and biological means. The deterioration of water quality cause the increasing growth of cat tail (Cabombafurcata) and the growth of water lily which can be easily found previously (Nelumbo nucfera) had currently decreasing. The NWQS for the lake in both seasons is in Class II while the WQI was classified under Class II which is slightly polluted. This shows that the lake is in degradation state which can cause long term deterioration if no drastic lake's restoration is carried out.